(untitled) - Leadbetter, Chris (Cambridge, UK, 2004)
This textbook has been written specifically for the CIE syllabuses in IGCSE Computer Studies and O Level Computer Studies, and IGCSE Information Technology. It is written by experienced teachers and examiners and endorsed by CIE, ensuring that it is up to date and comprehensive in its coverage of the syllabuses. The book offers valuable, practical support for students. It includes questions and tasks throughout to reinforce learning, and a selection of past examination questions to help students develop and practise their examination techniques. The authors have also included useful guidance on dealing with coursework tasks and practical assessments.
Keywords: Information technology.,Computer,Công nghệ thông tin,Tin học